Stenting and cell technologies in the treatment of atherosclerotic renovascular hypertension Part 3. Some genetic, pharmacological, and radio-ecological features of malignant renovascular hypertension - A. N. Kharlamov; Ya. L. Gablnsky; E. K. Bos; P. A. Davidovich; V. S. Veselova (Кардиоваскулярная терапия и профилактика)
Aim. To assess effectiveness and safety of pharmaceutical therapy, as well as genetic, pharmacogenetic, and radio-ecological features of malignant renovascular hypertension (RVH).Material and methods. Seventy-eight patients were randomized into main (n=26) and placebo groups (n=52). Primary combined end-point included the following: genetic analysis of monogenic disease, chromosome aberrations, genotypes and allele patterns for main polymorphic candidate genes participating in arterial hypertension (AH) and atherosclerosis pathogenesis; pharmacogenetic features of lipid-lowering and antihypertensive pharmaceutical therapy effectiveness; incorporated gamma-nuclide activity in critical organs.Results. Combined therapy with statins (target levels achieved in 92 % of the patients), fibrates (91 %), and angiotensin II antagonists (95 %) was highly effective and safe in RVH / ischemic nephropathy treatment. Genetic analysis demonstrated monogenic disease, adverse polymorphic gene genotypes, and chromosome aberrations linked to AH, atherosclerosis and metabolic syndrome (MS), in more than 30 % of the participants. Stem sell transplantation (SCT) resulted in a 7,1-fold increase in concentration of mononuclear cells with high telomerase activity and long telomeres. Higher prevalence of adverse genome characteristics in Ural population (by 2,7 times, comparing to Dutch population) could be partially explained by adverse radio-ecology in the former region: caesium, iodine, cobalt, manganese, and chrome concentrations were 12,6 times higher than their upper safety limits. SC could act as radionuclide discorporants, reducing radionuclide concentration by 1,4-2,3 times. Pharmacogenetic analysis demonstrated minimal gene polymorphism sensitivity and maximal effectiveness for the combination of fluvastatin forte and fenofibrate M (36 %), as well as valsartan (44 %).Conclusion. Pharmaceutical therapy was highly effective and safe in RVH / ischemic nephropathy treatment. Genetic analysis demonstrated monogenic disease, adverse polymorphic gene genotypes, and chromosome aberrations linked to AH, atherosclerosis and MS, in more than 30 % of the subjects.